Analisis Kontribusi Pendapatan Usahatani Padi terhadap kesejahteraan petani di Desa Ajubissue, Kecamatan Pitu Riawa, Kabupaten Sidenreng Rappang - Rasidin, Rasidin; Sumartan, Sumartan; Adelia, Dian; Munawarah, Munawarah (Universitas Galuh, 2025)
Rice is an important food commodity because it is a staple food and source of income for the Indonesian population. Ajubissue Village is a village where the majority of the people work as rice farmers. Efforts to increase rice production continue to be made by the government to maintain food availability and increase farmers' income and welfare. However, there are several urgent problems in Ajubissue Village, namely the low capacity of rice farmers in using rice farming production factors, the use of less superior seeds, the procurement of expensive production input facilities. , it is difficult for farmers to obtain fertilizer, as well as the lack of awareness of farmers in using optimal, efficient and effective production factors so that the productivity of the rice produced is still low and affects farmers' income which has an impact on the welfare of rice farmers. The urgency of this problem means that research on the Contribution of Rice Farmer Group Business Income to the welfare of rice farmers needs to be carried out in Ajubissue Village. The aim of this research is to analyze rice farming income and analyze how much rice farming income contributes to farmers' welfare. This research method is quantitative and qualitative, while the method used is a survey method. The research was conducted in Ajubissue Village, Pitu Riase District with a total of 30 rice farmers as respondents who were determined using the Simple Random Sampling Method. The data analysis tool method used is multiple regression with the Cobb-Douglass production function and income analysis and measuring the contribution of rice farming to the income of rice farmers in Ajubissue Village. Research was conducted for five months (May – September 2024) with the conclusion that rice farming contributed 68.57 percent to income with an average income obtained from rice farming of Rp24,515,600.